Wild Deer (Pudu Puda) from Chile Harbor a Novel Ecotype of Anaplasma Phagocytophilum - Moreira-Arce, D (BioMed Central Ltd, 2023)
Background: Deer species play an important role in the enzootic cycles of several Anaplasma species. While in the Northern Hemisphere ticks of genus Ixodes are well recognized vectors of these intracellular bacteria, less is known regarding the biological cycles of Anaplasma spp. in South America. Methods: Using PCR protocols and Sanger sequencing, we assessed the presence of Anaplasma spp. in blood and ticks collected on a native deer species (Pudupuda) from southern Chile. Results: Based on phylogenetic analyses of the 16S rRNA, gltA and groEL genes and calculation of average sequence divergence for groEL, our results bring to light a novel genovariant of Anaplasmaphagocytophilum (named strain “Patagonia”). The strain represents a novel ecotype within the A. phagocytophilum species complex and was detected in both P.puda and their ticks. Using a larger matrix, denser taxon sampling and outgroup, our maximum-likelihood- and Bayesian-inferred phylogenies for groEL provide an accurate picture of the topology of A. phagocytophilum ecotypes and their evolutionary relationships. Conclusions: This is the first report of an ecotype of A. phagocytophilum in South America. Our results provide novel insight into the genetic diversity and ecology of this complex of bacterial lineages. Further studies should elucidate the enzootic cycle of A. phagocytophilum strain “Patagonia” and assess its pathogenic potential for pudues, domestic animals and humans in the region. Graphical Abstract: [Figure not available: see fulltext.]. © 2023, The Author(s).